THE EFFECT OF COMPETENCIES, COMMITMENT ORGANIZATIONS, AND SUPERVISION ON THE PERFORMANCE OF BOARDING SCHOOL AL-AMIN MOJOKERTO - Nur Syamsudin (At-Taqaddum, 2017)
The objective of this study was to Assess the effect of competence, organizational commitment, and supervision simultaneously and partially on the performance of employees at the boarding school Al-Amin Mojokerto, and Revealing the factors which most influence on employee performance Pondok Pesantren Al-Amin Mojokerto. This research uses a descriptive quantitative approach with multiple linear regression methods. The sample used in this study is a sample of the population, meaning that all the population of research subjects. The technique of collecting data using questionnaires. From the results, if the data found that competence, organizational commitment, and monitoring the significant effect on the performance of employees at boarding school Al-Amin. This is evidenced by the results of the F test shows that F count larger than F table. Partially each independent variable namely competence, organizational commitment, and supervision significantly influence the dependent variable employee performance as evidenced by t where t is greater than t table.